HSV, Edge Preserved and Huffman Coding based Intra Frame High Efficient video Compression for Multimedia Communication - Sripal Reddy, K; Leelaram Prakash, B (International Journal of Engineering and Technology, 2018)
High Efficiency Video Coding (HEVC) is another pressure standard for high resolution video content, which just needs 50% of the bit rate of H.264/Advanced Video Coding (AVC) at the same perceptual quality. Be that as it may, the computational intricacy is increments dramatically to adopt quad-tree organized Coding Unit (CU). In this document a new Hue Saturation Lightness (HSV), Edge Preserving and Huffman coding (HC) based intra frame high efficient video compression algorithm is introduced which is named as HSV-EPHC-IFHEVC.Â  To increase the compression ratio of the video frames Huffman and Differential Pulse Code Modulation (DPCM) encodings are used. To improve the de-compressed frame quality in compression Sharpening filter based Edge preserving technique is used. This HSV-EPHC-IFHEVC algorithm provides much better performance compared to existing systems. The performance measurement is in the terms of MSE, PSNR, RMSE and Execution time.Â Â